The identification of CD4(+) T cell epitopes with dedicated synthetic peptide libraries - Hiemstra, Hoebert S. (The National Academy of Sciences of the USA, 1997)
For a large number of T cell-mediated immunopathologies, the disease-related antigens are not yet identified. Identification of T cell epitopes is of crucial importance for the development of immune-intervention strategies. We show that CD4(+) T cell epitopes can be defined by using a new system for synthesis and screening of synthetic peptide libraries. These libraries are designed to bind to the HLA class II restriction molecule of the CD4(+) T cell clone of interest. The screening is based on three selection rounds using partial release of 14-mer peptides from synthesis beads and subsequent sequencing of the remaining peptide attached to the bead. With this approach, two peptides were identified that stimulate the β cell-reactive CD4(+) T cell clone 1c10, which was isolated from a newly diagnosed insulin-dependent diabetes mellitus patient. After performing amino acid-substitution studies and protein database searches, a Haemophilus influenzae TonB-derived peptide was identified that stimulates clone 1c10. The relevance of this finding for the pathogenesis of insulin-dependent diabetes mellitus is currently under investigation. We conclude that this system is capable of determining epitopes for (autoreactive) CD4(+) T cell clones with previously unknown peptide specificity. This offers the possibility to define (auto)antigens by searching protein databases and/or to induce tolerance by using the peptide sequences identified. In addition the peptides might be used as leads to develop T cell receptor antagonists or anergy-inducing compounds.